Review of Gonatocerus (Hymenoptera: Mymaridae) in the Palaearctic region, with notes on extralimital distributions - Triapitsyn, Serguei V. (Zootaxa, 2013)
The Palaearctic species of the common and speciose fairyfly genus Gonatocerus Nees ab Esenbeck (Hymenoptera: My-maridae) are reviewed. Illustrated identification keys are provided to separate the three subgenera of Gonatocerus that oc-cur in the region and to females of the species in each subgenus. Distribution ranges, including new records of extralimital specimens examined, and known host associations of the species are given. Forty-two valid taxa are recognized including 19 newly described ones: two in G. (Gonatocerus)—G. bukashka sp. n. (Denmark, Russia) and G. koziavka sp. n. (Kyr-gyzstan), 15 in G. (Lymaenon Walker)—G. berezovskiyi sp. n. (Turkmenistan), G. beshbarmak sp. n. (Kyrgyzstan), G. ka-lika sp. n. (Denmark), G. karakum sp. n. (Italy, Turkmenistan), G. karlik sp. n. (China, Republic of Korea, Russia), G. katraps sp. n. (Republic of Korea, Russia), G. kazak sp. n. (Russia, Spain), G. komarik sp. n. (France), G. krasavchik sp. n. (Russia), G. kulik sp. n. (Russia), G. kum sp. n. (Russia), G. kusaka sp. n. (Russia), G. saulfrommeri sp. n. (Russia), G. svat sp. n. (China), G. ucri sp. n. (Russia), and two in G. (Cosmocomoidea Howard)—G. kikimora sp. n. (Russia) and G. woohoo sp. n. (Russia). New synonymies are proposed for the following names: G. (Gonatocerus) fuscicornis (Walker) [= G. sulphuripes (Foerster) syn. n., G. pictosimilis Soyka syn. n., Lymaenon synaptus Debauche syn. n., L. alecto De-bauche syn. n., and L. crassipes Debauche syn. n.]; G. (Gonatocerus) aegyptiacus Soyka [= G. saipanensis (Doutt) syn. n., G. alami Shamim & Shafee syn. n., G. tarae Narayanan & Subba Rao syn. n., G. miurai Sahad syn. n., and G. minor Matthews syn. n.]; G. (Gonatocerus) pictus (Haliday) [= G. orthopenitus Guo, Lin & Hu syn. n.]; G. (Lymaenon) aureus Girault [= G. tenuipennis Girault syn. n., G. chrysis (Debauche) syn. n., G. vopros nom. n. pro G. flavus Soyka, 1950 (nec G. flavus Foerster, 1841) syn. n., G. pahlgamensis (Narayanan) syn. n., G. kanheriensis Mani & Saraswat syn. n., G. grac-ilentus Hellén syn. n., G. aligarhensis Shamim & Shafee syn. n., and G. fukuokensis Sahad syn. n.]; G. (Lymaenon) lito-ralis (Haliday) [= Alaptus fuscus Förster syn. n., G. exiguus Förster syn. n., G. americanus Brues syn. n., G. anthonomi Girault syn. n., G. brunneus Girault syn. n., G. illinoiensis Girault syn. n., G. maevius Girault syn. n., G. texanus Girault syn. n., and G. priesneri Soyka syn. n.]; G. (Lymaenon) longior Soyka [= G. conicus (Mathot) syn. n.]; G. (Cosmoco-moidea) oxypygus Foerster [= G. ovicenatus Leonard & Crosby syn. n. and G. megalura (Mathot) syn. n.]. Lymaenon cunctator Mathot is reinstated as a valid species, G. (Lymaenon) cunctator (Mathot) stat. rev., based on study of its holo-type. Lectotypes are designated for Alaptus fuscus, Gonatocerus anthonomi, G. ater Foerster, G. brunneus, G. exiguus, G. texanus, Lymaenon fuscicornis Walker, L. tremulae Bakkendorf, and Rachistus sulphuripes Foerster. Neotypes are desig-nated for G. aureus and G. oxypygus.